Orientação para o mercado, inovação e performance organizacional sob os parâmetros da competitividade: um estudo no setor hoteleiro do Rio Grande do Sul - Caporal, Gibsy Lisiê Soares (2005)
This paper examines the market orientation, innovation and organizacional performance from competitive parameters, adapted from Sandvik & Sandvik (2003) to the reality of hospitality companies of the Rio Grande do Sul. Through a descriptive research of transversal cut and based on the analysis of the data, the differences of averages of answers applying test- F, demonstrated that the majority of the searched hotels is in the market for 10 years and that 50% are small business companies. Moreover, 70% of the hospitality companies adopted as competitive strategy the adaptation to the necessities and demands of the customers. One evidenced is that the capacity of the hospitality companies in innovating for the market and for the companies happens independently of its competitive adoption, however considering market orientation and organizacional performance some elements had shown different behaviors, that had rejected the initial hypothesis. The research design consisted on Introduction, Theoretical Research, where the constructs and concepts are detached giving bases to the study, and Methodology. Finally, the Results descriptions of the survey, ending with final considerations in the Conclusion.